FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SIKAP REMAJA KELAS XI TERHADAP HUBUNGAN SEKSUAL PRANIKAH (INTERCOURSE) DI SMA DHARMA BAKTI MEDAN TAHUN 2014 - Saragih, Hanna Sriyanti; Sianturi, Rika Dinata; Sitepu, Jujuren (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2014)
The lack of information received by adolescents about reproductive health and lack of knowledge causes an effect on adolescent attitudes toward sexual behavior. Destination of the research for factors associated with adolescent attitudes toward class xi premarital sexual relations (intercourse) Medan of Dharma Bakti Senior High School year 2014. The role of parents also influence adolescent attitudes toward premarital sexual relations. Additionally teenagers often receive information about sex instead of one source, even misleading, for example, of the mass media that actually abused by teens. This research is analytic approach to cross-sectional design with a sample size of 60 respondents. Data were analyzed using univariate and bivariate Chi-Square test. The analysis showed that factors associated with adolescent attitudes toward premarital sexual intercourse in high school is Dharma Bakti field of reproductive health knowledge p value = 0,005 (<0,05), the role of parents p value = 0,001 (<0,05), the role of the mass media p value = 0,010 (<0,05). It is expected that the school can make this research as a guide to improve the provision of information or education about reproductive health especially about sex education for adolescent in school.